Nursing infant with acquired toxoplasmosis in the first months of life – a case report - Hanstter Hallison Alves Rezende; Heloísa Ribeiro Storchilo; Jaqueline Ataíde Silva Lima; Antônio Roberto Gomes Júnior; Taynara Cristina Gomes; Jéssica Yonara de Souza; Mariza Martins Avelino; Waldemar Naves do Amaral; Marina Clare Vinaud; Ana Maria de Castro (Revista do Instituto de Medicina Tropical de São Paulo, 2017)
ABSTRACT Toxoplasmosis is caused by Toxoplasma gondii and the probability of this infection occurring in the first months of life is usually low because its transmission is related to eating habits. A 6-month-old nursing infant was diagnosed with acute toxoplasmosis, which was identified through anti- T. gondii IgA, IgM and low-avidity IgG serologic assays, polymerase chain reaction (PCR) and mouse bioassay test although its mother was seronegative. This serological divergence between mother and child led us to interview the mother regarding epidemiological factors. During this interview, she reported that she had given her 2-month-old baby a piece of undercooked beef to suck on. After some time, the baby presented fever and cervical lymphadenitis. This report emphasizes the importance of serological surveys of toxoplasmosis in nursing infants presenting with fever and lymphadenitis, in view of the possible acquisition of toxoplasmosis in the first months of life.